2021
DOI: 10.1002/jctb.6645
|View full text |Cite
|
Sign up to set email alerts
|

Particle size distribution as a major characteristic of domestic wastewater: implications for the modeling and design of membrane bioreactors

Abstract: This study reviews the evolution of the concept and the methodology of particle size distribution (PSD) analysis for sewage. Evaluation of experimental data indicated that the analytical approach started with an empirical identification of soluble, colloidal and supra‐colloidal organic matter. Then, it evolved into a sequential filtration and ultrafiltration methodology, yielding results useful enough to be an integral complement of respirometric chemical oxygen demand (COD) fractionation based on biodegradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 81 publications
1
13
0
Order By: Relevance
“…This does not pose a problem, mainly because the magnitude of S I is usually 3-5% for sewage, much lower than the 12% indicated in the figure, involving a negligible effect on the prediction of S H . 20 Therefore, the results provided a sustainable ground to suggest that a reliable PSD analysis could be used for model evaluation and treatment design without the need for complex respirometric assessment of COD fractionation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This does not pose a problem, mainly because the magnitude of S I is usually 3-5% for sewage, much lower than the 12% indicated in the figure, involving a negligible effect on the prediction of S H . 20 Therefore, the results provided a sustainable ground to suggest that a reliable PSD analysis could be used for model evaluation and treatment design without the need for complex respirometric assessment of COD fractionation.…”
Section: Discussionmentioning
confidence: 93%
“…17 Dulekgurgen et al 18 proposed and tested a new experimental technique of sequential filtration to assess the particle size distribution (PSD) of COD in sewage, which could be evaluated as an index for biodegradability; Noyan et al 19 used the same approach to reveal the inherent relationship between PSD analysis and COD fractionation in sewage. A recent review also evaluated all available information on sewage to suggest default values of different COD fractions with corresponding size intervals 20 ; the default values indicated that an average of (i) 65% of total COD in sewage was of particulate nature (>450 nm) including inert particulate COD, X I , and slowly biodegradable COD, X S , fractions; and (ii) 35% of the total COD was in the soluble range with a soluble hydrolysable COD, S H , of 20% within a 2.0-220 nm range and the remaining 15% accounted for readily biodegradable COD, S S , and soluble inert COD, S I , fractions (<2.0 nm). It is clear that this type of evaluation could be a valuable asset for biological treatment; however, no studies have so far been conducted to interpret the performance of plain or chemically enhanced settling in terms of the resulting PSD profile and COD fractionation in treated sewage.…”
Section: Introductionmentioning
confidence: 99%
“…29 COD fractionation continues to be extensively studied for domestic wastewaters, especially for Istanbul sewage. A recent review compiled COD fractionation results for sewage with the main purpose of evaluating their relationship with particle size distribution; 30 the review also provided a default COD fractionation profile, which is worth being considered for the respective ratios of different COD components. For this study, COD fractionation results experimentally determined at different discharge points (Baltalimanı, Kadıköy, Ataköy, Yenikapı) in Istanbul, [30][31][32][33][34][35] including that of the Ambarlı sewage, 36 are listed in Table 3.…”
Section: Cod Fractionationmentioning
confidence: 99%
“…Simulation of the SFAS behaviour and performance requires relevant numerical information on COD fractionation of sewage and on the kinetic characteristics of processes defining the interactions between substrate and biomass that will be used as model components and coefficients. Studies on COD fractionation are well described in a recent review that proposed default values on the relative magnitude of different COD fractions 42 . Accordingly, the values adopted in Table 5 define a typical sewage with a particulate COD content of 65%.…”
Section: Model Interpretation Of System Performancementioning
confidence: 99%
“…wileyonlinelibrary.com/jctb on the relative magnitude of different COD fractions. 42 Accordingly, the values adopted in Table 5 define a typical sewage with a particulate COD content of 65%. The selection of numerical values for the kinetic coefficients involved a comprehensive review of the available information and the average levels of the reported experimental data, as summarized in Table 6, were used in the simulation exercise.…”
Section: Model Interpretation Of System Performance Model Structurementioning
confidence: 99%